Housing Stigmatization: A General Theory - Horgan, Mervyn (2020)
This article treats housing stigmatization as a social process of symbolic ascription, connected to inhabitants, housing form, housing tenure, and/or housing location. Stigmatization research tends to focus on personal stigmatization, or to examine housing only in relation to territorial stigmatization, while housing research tends to focus on health and policy. This article demonstrates that housing stigmatization, which is differentiated from personal stigmatization and territorial stigmatization, is a viable unit of analysis in its own right for stigma research. Seven core elements are identified, showing that housing stigmatization is: (1) relational; (2) contextual; (3) processual; (4) reinforceable; (5) reversible; (6) morally loaded; and (7) treated as contagious. Comprehending the elements of housing stigmatization will benefit destigmatization efforts.